WIL-2 NS LYMPHOMA CELL LINE SHOW APOPTOTIC FEATURES WHEN TREATED WITH TRADITIONAL MEDICINE COMMELINA BENGHALESIS - Mokgotho, M. P.; Masoko, P.; Mbazima, V. G.; Lebogo, K. W.; Mampuru, L. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Many natural occurring agents have shown chemo preventive and chemotherapy potentials, yet there are no effective drugs to treat most cancers. Commelina benghalensis has been traditionally used as a herbal plant whose leaves are believed to have anti-tumour properties. The aim of this study was to investigate the effect of semi-purified extracts from C. benghalensis on the proliferation of Wil-2 NS cells. An acetone extract was prepared from the leaves and defatted with n-hexane and fractionated with dichloromethane (F2). F2 was tested for anti-proliferative activities on Wil-2 NS cells. Results from the trypan blue exclusion and sulphorhodamine B assays showed F2 inhibited the proliferation of the Wil-2 NS cells in a dose and time dependent manner. The acridine orange/ethidium bromide dual stain showed that the treated cells die through a process of apoptosis. These results show that C. benghalesis has anti-proliferation properties against Wil-2NS lymphoma cells. Further studies are required to determine the components responsible from the extracts and elucidate the mechanism of action on growth inhibition. Acknowledgements: NRF and University of Limpopo Research office.